Telefoner och telefonsamtal - Garnert, Jan (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2001)
The article presents and discusses Jan Garnert’s research project "Calling for a Meaning", in which he investigates the cultural history of telephony, i.e. the cultural and social meanings of telephone calls. This is done in two case studies. The first case study takes its starting point in Stockholm in the 1870’s, a time when people in order to communicate as a rule had to meet in person. The introduction of the telephone changed this basis for human networks and social interaction in the 1880’s by making it possible to engage in conversations even with persons in places out of earshot. What meanings did this technological change have for people’s understanding of time and space and for their social relations? The second case study explores the last two decades of the 20th century when telephones more and more were connected to individuals, and not to places. What meanings did this have for the perceptions and uses of time and space? What will it mean for networks among friends, family relations, and business connections?